Design of Clinical Trials Evaluating Sedation in Critically Ill Adults Undergoing Mechanical Ventilation: Recommendations From Sedation Consortium on Endpoints and Procedures for Treatment, Education, and Research (SCEPTER) Recommendation III. Issue 10 (29th April 2021) - Ward, Denham S.; Absalom, Anthony R.; Aitken, Leanne M.; Balas, Michele C.; Brown, David L.; Burry, Lisa; Colantuoni, Elizabeth; Coursin, Douglas; Devlin, John W.; Dexter, Franklin; Dworkin, Robert H.; Egan, Talmage D.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Clinical trials evaluating the safety and effectiveness of sedative medication use in critically ill adults undergoing mechanical ventilation differ considerably in their methodological approach. This heterogeneity impedes the ability to compare results across studies. The Sedation Consortium on Endpoints and Procedures for Treatment, Education, and Research Recommendations convened a meeting of multidisciplinary experts to develop recommendations for key methodologic elements of sedation trials in the ICU to help guide academic and industry clinical investigators. DESIGN: A 2-day in-person meeting was held in Washington, DC, on March 28–29, 2019, followed by a three-round, online modified Delphi consensus process. PARTICIPANTS: Thirty-six participants from academia, industry, and the Food and Drug Administration with expertise in relevant content areas, including two former ICU patients attended the in-person meeting, and the majority completed an online follow-up survey and participated in the modified Delphi process. MEASUREMENTS AND MAIN RESULTS: The final recommendations were iteratively refined based on the survey results, participants' reactions to those results, summaries written by panel moderators, and a review of the meeting transcripts made from audio recordings. Fifteen recommendations were developed for study design and conduct, subject enrollment, outcomes, and measurement instruments. Consensus recommendations included obtaining input from ICU survivors and/or their families, ensuring adequate training for personnel using validated instruments for assessments of sedation, pain, and delirium in the ICU environment, and the need for methodological standardization. CONCLUSIONS: These recommendations are intended to assist researchers in the design, conduct, selection of endpoints, and reporting of clinical trials involving sedative medications and/or sedation protocols for adult ICU patients who require mechanical ventilation. These recommendations should be viewed as a starting point to improve clinical trials and help reduce methodological heterogeneity in future clinical trials.